THE NAIB AS-SALTANA, END OF THEIR TENURE AND ITS CONSEQUENCES IN THE PERİOD OF BAHRI MAMLUKS (1250-1382) - M. Fatih YALÇIN (Fırat University, 2019)
During the Mamluk period, naib as-saltana was only second to the sultan himself and was the highest ranking officer. The duty of this powerful amir ended by different means in the Bahri Mamluk period. It is understood that their duty may end with different reasons such as death, resignation, appointment to an another post, arrestment and becaming sultan himself. In addition, it is necessary to underline that their time of office also varies. In the period of study, it is seen that the office of naib as-saltana ends with different reasons. The most important reason for their dismission is the increase of their power and their acts which disturbs the sultan and other high-ranking officials. As a result, naib as-saltana was seen as a threat to the crown, other amirs’ provocations of sultan and their incapacity were among the causes of the dismission of naib as-saltana. On the other hand, there were some naib as-saltanas who became sultans as a result of their achievements. Among the naib as-saltana, some resigned from their post, someother were appointed to other posts, the rest were killed or imprisoned or died on the post. In the Bahri Mamluks, amirs, atabek, were influential for the dismissal and appointment of naib as-saltana. After their dismissal, the naib as-saltana was appointed to the lower administrative posts such as deputy of Aleppo and Damascus. In addition, few of them were appointed to the posts outside Egypt. Among the naib as-saltana, ten were punished by imprisonment or death and four died on the post. The imprisonment penalty was applied in Alexandria and Kerek.